Can Group B Streptococci Cause Symptomatic Vaginitis?. Issue 4 (1999) - Honig, E.; Mouton, J. W.; van der Meijden, W. I.
Abstract : Background: Maternal cervicovaginal colonization with Lancefield group B streptococci (GBS) is an important risk factor for neonatal morbidity and mortality. About 15% of women are carriers of GBS. Usually, they are asymptomatic. Cases: We describe two patients with symptomatic vaginitis for which no apparent cause was found. Both patients were heavily colonizedwith GBS. After antibiotic treatment, both became asymptomatic and culture negative, but after recolonization with GBS, symptoms resumed. This phenomenon was repeatedly observed. After emergence of resistance to antibiotics, local application of chlorhexidine appeared to be the only useful treatment. Conclusion: We hypothesize that GBS-vaginitis may be a possible disease entity. Although at present it is not clear why some patients become symptomatic, we speculate that the immunologic response is somehow selectively hampered in such patients. Infect. Dis. Obstet. Gynecol. 7:206–209, 1999.